Ethical Violations in Business Practices on Social Commerce: Insights from Quranic Verses - Muhammadun, Muzdalifah; Pabbajah, Mustaqim; Yunus, Mukhtar; ., Suarning; Adawiah, Rabiatul (Journal of Ecohumanism, 2024)
The advancement of technology has resulted in a decline in business ethical standards, particularly within the realm of online trading on social commerce. However, this phenomenon tends to be neglected in Islamic economic studies. This study responds to the shortcomings of existing studies by focusing on explaining and reflecting on how violations of Qur'anic business ethics occur in online trading on social commerce. In order to address these issues, this study employs a descriptive qualitative approach utilising the content analysis method. The findings of this study indicate three significant contexts in which violations of Quranic business ethics in online trading on social commerce occur. Firstly, ghorar, which occurs in misleading product descriptions and hidden fees, is employed to manipulate consumer behaviour through deceptive marketing tactics. Secondly, maisir, which takes the form of exploitation and the creation of a "viral trend" culture that could lead to impulsive and potentially unethical purchasing decisions, is a further issue. Thirdly, zolim, which takes the form of deceptive marketing practices, unfair pricing, or the exploitation of vulnerable consumers, is also a concern. These three findings collectively demonstrate that the advent of technology has negatively impacted the ethical standards observed in Qur'an business practices. Furthermore, this study recommends that further research be conducted to investigate the potential for technology to mitigate the negative consequences of online sales.